Analyzing Negative Advertisements from Legal Framework in Indonesia and The Impact on Indonesia Business - Pramono, Ardiyanto; Mumpini, Danandaka (Universitas Proklamasi 45, 2023)
Negative advertisement has been a marketing strategy in Indonesia’s business world. However, the debate around this strategy has occurred due to divided opinion. While several parties agreed that it is a common practice, others are against negative advertisements since the impact will corrupt the vision of a sustainable economy in Indonesia entirely and have negative impacts on the development of Indonesian business. This research analyses the legality of negative advertisements in Indonesia in various contexts, such as Consumer Protection Law, Information and Electronic Transaction Law, and Fair Business Competition Law.Later, the research will discuss the impacts of existing laws on negative advertisements and recommendations on how to tackle the negative impacts of negative advertisements. Finally, the research is done by the normative-judicial method. It explores the element of law-sociology to explain the phenomenon of negative advertisement and the future impacts due to the flaws of existing laws.